(untitled) (Asian Business Research, 2022)
With the further establishment of the scientific development concept of "green water and green mountains are golden mountains and silver mountains", tourism has become an important part of the tertiary industry and an important way for urban development, poverty alleviation and prosperity. It is known as the "sunrise industry". During the epidemic period, even if the tourism industry and its related catering and accommodation fields are greatly impacted, the tertiary industry is still the driving force for maintaining local macroeconomic stability in all regions of China and the key to the victory of the "battle against poverty". Based on the modeling of non-stationary time series, this paper establishes cointegration and error correction models for the relationship between urban and rural residents’ domestic tourism consumption, residents’ income and social security, in order to put forward reasonable suggestions and measures on how to restore tourism in different regions after the epidemic. The innovation of this paper is to compare rural areas with urban areas, and explore and analyze the different effects and paths of influencing factors. The conclusion of this paper is that for urban residents, the policy of increasing residents’ income or reducing personal tax to increase disposable income can better stimulate urban residents’ tourism consumption, while residents in rural areas pay more attention to social welfare and security, Therefore, the economic recovery of tourism in the later stage of the epidemic should be developed according to local conditions and different consumer groups.